Enzymatic Bioweathering and Metal Mobilization From Black Slate by the Basidiomycete Schizophyllum commune - Kirtzel, Julia; Madhavan, Soumya; Wielsch, Natalie; Blinne, Alexander; Hupfer, Yvonne; Linde, Jörg; Krause, Katrin; Svatoš, Aleš; Kothe, Erika (Frontiers in Microbiology, 2018)
Schizophyllum commune is a filamentous basidiomycete causing white-rot in many wood species with the help of a broad range of enzymes including multicopper oxidases such as laccases and laccase-like oxidases. Since these enzymes exhibit a broad substrate range, their ability to oxidatively degrade black slate was investigated. The proteome during decomposition of black slate provides insight into molecular mechanisms that lead to the identification of potential proteins involved in rock degradation and stress resistance. Two laccases and four laccase-like oxidases were selected from the genome and studied for differential regulation at gene and protein level on black slate. On this stone, rich in organic carbon, up-regulation of laccase-like multicopper oxidase mco2 was found for the haploid monokaryon and the mated dikaryon. Both life forms were able to crack the rock and produce smaller particles. While the release of organic carbon provided an additional carbon and energy source, metals retained in this fraction of the slate were released and, after reaching a threshold concentration, inhibited a further growth of the fungus.